2018
DOI: 10.1111/jocn.14614
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness assessment: A questionnaire of current neuroscience nursing practice in Europe

Abstract: Aims and objectives: To study practice in consciousness assessment among neuroscience nurses in Europe.Background: Over the years, several instruments have been developed to assess

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Neurological assessment is part of the daily routine for most nurses working in neurology departments. This study con rm the results of previous study (Vink et al, 2018), that nurses with specialist education and training in neuroscience nursing have higher competence in consciousness assessment than nurses who only have basic education. It was evident in this study that most of participants have been using a standardized instrument and report the outcome of the assessment with both total scores and sub scores.…”
Section: Discussionsupporting
confidence: 91%
“…Neurological assessment is part of the daily routine for most nurses working in neurology departments. This study con rm the results of previous study (Vink et al, 2018), that nurses with specialist education and training in neuroscience nursing have higher competence in consciousness assessment than nurses who only have basic education. It was evident in this study that most of participants have been using a standardized instrument and report the outcome of the assessment with both total scores and sub scores.…”
Section: Discussionsupporting
confidence: 91%
“…Nurses in neurological wards or intensive care units showed a higher neurological assessment ability compared with other clinical area nurses (Waterhouse, ). Conversely, one European survey found no significant difference between bedside nurses and nurses in other positions, levels of education, or institution type (Vink et al, ). The reason for the low assessment competency found in our study can be explained by the difference in the length of current work experience and the frequency of using competencies between the emergency department and intensive care unit nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have also highlighted the suboptimal neurological assessment competency in assessing the consciousness level (Brunker & Harris, 2015), cerebellar function (Kim et al, 2016), application of the Glasgow Coma Scale (Waterhouse, 2008), pupil size interpretation (Brunker & Harris, 2015;Kerr et al, 2016), and bedside nursing neurological assessment practice (Kirschen et al, 2018). Standardized practice in the use of assessment scales is needed, because the greatest variation existed in training methods for the use of the instruments (Kirschen et al, 2019;Vink et al, 2018). Nurses have shown low neurological assessment competency because of fragmented curriculum allocations for neurological assessment and neurological disorders (Shin et al, 2017;Zarandona, Hoyos Cillero, & Arrue, 2019 (Dancer, Brown, & Yanase, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was carried out in Europe, which identified that 95% of nurses applied GCS as the main Nursing intervention to assess the level of consciousness of patients with brain injuries. 16 Pupil assessment is considered to be the standard procedure for assessing neuro-critical patients and was performed in 79.7% of the patients in this study. In a study with 76 individuals with neurological injury admitted to an ICU, pupilometry readings hourly, identifying that pupilometer values correlated significantly with ICP values, concluding that routine pupillometric assessments in care neuro-critical patient is a valuable complement to the monitoring of ICP, as it reflects a balance of intracranial contents and a good indicator of increased ICP.…”
Section: Discussionmentioning
confidence: 99%